The effect of institutional quality on foreign direct investment - Al Mustofa, Muhammad Ubaidillah; Sukmana, Raditya (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study analyzes the impact of institutional quality on foreign direct investment (FDI). We apply panel regressions on a sample of 13 Organization of Islamic Cooperation (OIC) countries over 2002 – 2019. The empirical results show that institutional quality plays a vital role in determining the flow of foreign investments. Specifically, better regulatory quality tends to increase the inflow. The findings further show that countries with higher Gross Domestic Products (GDP) have greater capacity to attract larger investment flows. Additionally, a lower tax rate is expected to encourage the inflow of foreign investments. Finally, there is evidence that corruption encourages greater inflow of FDI.